The Importance of Trust and Maintaining Commitment to Couples in Long Distance Marriages - Aprilia, Bella Nadia; Rahayu, Diah; Rifayanti, Rina (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
Long-distance marriage in couples has problems that are quite risky considering the quantity of communication and gathering is reduced. This requires strengthening commitment so that long-distance marriages can run, and marriages survive. This commitment is thought to be influenced by the strong factor of trust in other partners. Therefore, this study aims to answer the assumption that trust is closely related to long-distance marriage commitment. This research method uses quantitative with purposive sampling techniques that have research subjects as many as 101 pairs. The measuring instruments used are the Commitment scale with a reliability of 0.860 and the Confidence scale with a reliability of 0.899. Both measuring instruments have good reliability and are analyzed using Pearson Product Moment. The results of this study showed that the higher the trust, the stronger the marriage commitment in couples who underwent long-distance marriages. This research shows the implication that long-distance couples should strengthen commitment by increasing trust, which includes the ability of the couple to predict the ability of each partner to assess the possibilities that occur long-distance activity, then the level of dependence means that the couple feels mutual need for each other, and confidence in the partner means that each partner trusts each other, supports each other Other.Pernikahan jarak jauh pada pasangan memiliki permasalahan yang cukup riskan mengingat secara kuantitas komunikasi dan berkumpul bersama menjadi berkurang. Hal ini dibutuhkan penguatan komitmen agar pernikahan jarak jauh dapat berjalan dan pernikahan tetap bertahan. Komitmen ini diduga dipengaruhi oleh faktor kuatnya kepercayaan terhadap pasangan lain. Oleh sebab itu penelitian ini bertujuan menjawab dugaan bahwa kepercayaan berhubungan erat dengan komitmen pernikahan jarak jauh. Metode penelitian ini menggunakan kuantitatif dengan Teknik sampling purposive sampling yang memiliki subjek penelitian sebanyak 101 pasangan. Alat ukur yang digunakan adalah skala Komitmen dengan reliabilitas 0.860 dan skala Kepercayaan dengan reliabilitas 0.899, kedua alat ukur ini memiliki reliabilitas yang baik dan dianalisis menggunakan Pearson Product Moment. Hasil penelitian ini menunjukkan bahwa semakin tinggi kepercayaan maka komitmen pernikahan semakin kuat pada pasangan yang menjalani pernikahan jarak jauh. Penelitian ini menunjukkan implikasi bahwa pasangan jarak jauh harus menguatkan komitmen dengan meningkatkan kepercayaan yang meliputi kemampuan predikbilitas pasangan artinya kemampuan tiap pasangan untuk mengkaji kemungkinan-kemungkinan yang terjadi akhibat jarak jauh kemuadian tingkat ketergantungan artinya bahwa pasangan merasa saling membutuhkan antara yang satu dengan yang lainnya dan keyakinan terhadap pasangan artinya bahwa setiap pasangan saling percaya saling mendukung satu sama lainnya.